Evaluation of Central Auditory Discrimination Abilities in Older Adults - Freigang, Claudia; Schmidt, Lucas; Wagner, Jan; Eckardt, Rahel; Steinhagen-Thiessen, Elisabeth; Ernst, Arne; Rübsamen, Rudolf (Frontiers in Aging Neuroscience, 2011)
The present study focuses on auditory discrimination abilities in older adults aged 65–89 years. We applied the “Leipzig inventory for patient psychoacoustic” (LIPP), a psychoacoustic test battery specifically designed to identify deficits in central auditory processing. These tests quantify the just noticeable differences (JND) for the three basic acoustic parameters (i.e., frequency, intensity, and signal duration). Three different test modes [monaural, dichotic signal/noise (s/n) and interaural] were used, stimulus level was 35 dB sensation level. The tests are designed as three-alternative forced-choice procedure with a maximum-likelihood procedure estimating p = 0.5 correct response value. These procedures have proven to be highly efficient and provide a reliable outcome. The measurements yielded significant age-dependent deteriorations in the ability to discriminate single acoustic features pointing to progressive impairments in central auditory processing. The degree of deterioration was correlated to the different acoustic features and to the test modes. Most prominent, interaural frequency and signal duration discrimination at low test frequencies was elevated which indicates a deterioration of time- and phase-dependent processing at brain stem and cortical levels. LIPP proves to be an effective tool to identify basic pathophysiological mechanisms and the source of a specific impairment in auditory processing of the elderly.